2016
DOI: 10.1016/j.njas.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agricultural extension service on adoption of chemical fertilizer: Implications for rice productivity and development in Ghana

Abstract: Given the increasing tension between food production and food demand in sub-Saharan Africa, as well as the poor development of the rice sector in Africa, the present paper examines the impact of agricultural extension on adoption of chemical fertilizers and their impact on rice productivity in Ghana. A parametric approach was employed to account for selectivity and endogeneity effects, which most impact studies fail to address. The empirical results reveal that agricultural extension service is endogenous in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
92
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 24 publications
16
92
3
3
Order By: Relevance
“…For instance, the majority of the farmers were able to decide for insecticide application when larval stages were at early (smaller) this mean farmers were aware on when to apply insecticides. The present survey is agreement with Mohammadrezaei & Hayati (2015); Lukuyu et al (2012); Benjamin (2013); Baloch & Thapa (2016) and Emmanuel et al (2016) who believed that agricultural extension services are the main diffusion technology instruments which impacts on farmers' knowledge and skills as well as on production. Daniel et al (2011) reported that training in pest epidemiology and crop management improved farmers' knowledge and led to better understanding of the pest epidemiology, so that the incidence of pests declined and cocoa yields increased by an average of 30%.…”
Section: Insectsupporting
confidence: 91%
“…For instance, the majority of the farmers were able to decide for insecticide application when larval stages were at early (smaller) this mean farmers were aware on when to apply insecticides. The present survey is agreement with Mohammadrezaei & Hayati (2015); Lukuyu et al (2012); Benjamin (2013); Baloch & Thapa (2016) and Emmanuel et al (2016) who believed that agricultural extension services are the main diffusion technology instruments which impacts on farmers' knowledge and skills as well as on production. Daniel et al (2011) reported that training in pest epidemiology and crop management improved farmers' knowledge and led to better understanding of the pest epidemiology, so that the incidence of pests declined and cocoa yields increased by an average of 30%.…”
Section: Insectsupporting
confidence: 91%
“…For the promotion of modern technologies and good agricultural practices, well-functioning and accessible extension services are imperative (Emmanuel et al 2016). However, in reality, extension services in SSA are often understaffed, underequipped and often lack the relevant knowledge on, for instance, weed management (e.g.…”
Section: The Status Quo Of Herbicides In Africamentioning
confidence: 99%
“…Access to extension was also found to improve productivity of value adders in the study. This follows productivity literature where extension services led to the dissemination of information that may be productivity-increasing for the farmers [66].…”
Section: Productivity Impact Of Value Addition Across Cassava Productmentioning
confidence: 98%
“…Moreover, the coefficient of access to extension was negative and significant in determining the productivity of the farmers. In their study, [66] found that the impact of extension on productivity came through farmers adopting the improved technology brought by extension. Hence, the negative effect of extension on productivity of the non-value adders may be suggestive of the decision not to add value in spite of possible contact with extension.…”
Section: Productivity Impact Of Value Addition Across Cassava Productmentioning
confidence: 99%